Immunological Responses to Tetanus and Influenza Vaccination in Donkeys - Maciej Perzyna; Jowita Grzędzicka; Dominika Milczek‐Haduch; Izabela Dąbrowska; Michał Trela; Bartosz Pawliński; Olga Witkowska‐Piłaszewicz (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Donkeys are routinely vaccinated with protocols developed for horses, yet species‐specific data on their immune responses are limited. Hypothesis/Objectives We hypothesized that donkeys exhibit robust T‐cell‐mediated immunity and regulatory adaptation after vaccination, comparable to horses. Animals Thirty‐six healthy, seronegative donkeys (34 mares, 2 stallions), aged 0.5–23 years (median 8 years), from two farms with similar housing and management conditions. Methods Prospective study. Animals were selected based on clinical health assessment and confirmed seronegativity for tetanus and equine influenza. All received a multivalent vaccine containing tetanus toxoid and equine influenza antigens. Blood samples were collected at baseline, 1 month, and 2 months after vaccination. Flow cytometry assessed CD4+, CD8+, and CD4 + FoxP3+ T cells (primary outcomes), and monocyte subsets and B lymphocytes (PanB/CD21+) with intracellular IL‐10, IL‐17, and Ki67 (secondary outcomes). ANOVA with Bonferroni correction (p < 0.05) was used for statistical analysis. Results CD4+ T cells increased from 25.1% ± 1.4% to 37.3% ± 0.7% at month 1, CD8+ from 20.6% ± 1.5% to 32.2% ± 0.9% at month 2 (p < 0.001). CD4 + FoxP3+ peaked at 11.7% ± 0.6% at month 1 (baseline 6.8% ± 0.8%), then returned to baseline. CD14 + MHCII+ and CD14 + MHCII− monocytes declined; CD14 − MHCII+ increased (p < 0.01). PanB/CD21+ cells decreased from 41.5% ± 1.8% to 29.0% ± 1.0%, with significant reductions in IL‐10+, IL‐17+, and Ki67+ subsets (p < 0.001). Conclusions and Clinical Importance Donkeys exhibit strong T‐cell and regulatory immune responses after vaccination, supporting the clinical relevance of applying equine vaccination protocols to donkeys.